Spatio‐temporal variability of warm rain events over southern West Africa from geostationary satellite observations for climate monitoring and model evaluation. (25th October 2018) - Young, Matthew P.; Chiu, J. Christine; Williams, Charles J. R.; Stein, Thorwald H. M.; Stengel, Martin; Fielding, Mark D.; Black, Emily
Abstract : This article presents the spatio‐temporal variability of warm rain events over southern West Africa (SWA) during the summer monsoon season for the first time, using Spinning Enhanced Visible Infrared Radiometer (SEVIRI) observations on the Meteosat geostationary satellites. The delineation of warm rain events is based on the principle that precipitating low‐level clouds are associated with either sufficient water content or large cloud droplet size. Capitalising on the ability of space‐borne radar to resolve vertical cloud structures and detect the presence of precipitation, the delineation is trained by collocated SEVIRI and CloudSat observations. The resulting 12 years of observations from SEVIRI are used to examine the spatial, diurnal, seasonal and interannual variability of warm rain events over SWA. Warm rain events predominate during the monsoon in August, with little interannual variability, and persist over orography in the morning and the coasts after midday, likely enhanced by orographic lifting and land–sea breeze effects. Warm clouds have a much higher probability of precipitation along the coastlines of Liberia and Nigeria compared to the central SWA coastline and further inland. Finally, when evaluating an 8‐day yet high‐spatial resolution model simulation, we find that warm rain frequencies from the simulation agree well with SEVIRI near the coast but simulated warm cloud cover and thus warm rain frequencies are too low over the Gulf of Guinea. The probability of precipitation of warm clouds is also too low inland. The newly developed observations of warm rain create opportunities to further investigate the diurnal cycle of warm rain, study aerosol–cloud–precipitation interactions, and assess the role of warm rain in the water cycle across Africa and beyond. Abstract : During the monsoon, warm clouds frequently cover a large proportion of southern West Africa, affecting the surface energy balance and water cycle. Quantifying how frequently these warm clouds rain is therefore important, to understand their lifetime and representation in models. Using geostationary satellite retrievals, we present a high‐resolution climatology of warm rain frequency which reveals frequent warm rain over coastal and orographic regions. We also illustrate the capability of using these retrievals for model evaluation.